Activation of mitochondrial transient receptor potential vanilloid 1 channel contributes to microglial migration. Issue 10 (23rd May 2015) - Miyake, Takahito; Shirakawa, Hisashi; Nakagawa, Takayuki; Kaneko, Shuji
<x xml:space="preserve">Abstract</x> Microglia, the resident immune cells in the brain, survey the environment of the healthy brain. Microglial migration is essential for many physiological and pathophysiological processes. Although microglia express some members of the transient receptor potential (TRP) channel family, there is little knowledge regarding the physiological roles of TRP channels in microglia. Here, we explored the role of TRP vanilloid 1 (TRPV1), a channel opened by capsaicin, heat, protons, and endovanilloids, in microglia. We found that application of capsaicin induced concentration‐dependent migration in microglia derived from wild‐type mice but not in those derived from TRPV1 knockout (TRPV1‐KO) mice. Capsaicin‐induced microglial migration was significantly inhibited by co‐application of the TRPV1 blocker SB366791 and the Ca2+ chelator BAPTA‐AM. Using RT‐PCR and immunocytochemistry, we validated that TRPV1 was expressed in microglia. Electrophysiological recording, intracellular Ca2+ imaging, and immunocytochemistry indicated that TRPV1 was localized primarily in intracellular organelles. Treatment with capsaicin induced an increase in intramitochondrial Ca2+ concentrations and mitochondrial depolarization. Furthermore, microglia derived from TRPV1‐KO mice showed delayed Ca2+ efflux compared with microglia derived from wild‐type mice. Capsaicin‐induced microglial migration was inhibited by membrane‐permeable antioxidants and MAPK inhibitors, suggesting that mitochondrial TRPV1 activation induced Ca2+‐dependent production of ROS followed by MAPK activation, which correlated with an augmented migration of microglia. Moreover, a mixture of three endovanilloids augmented microglial migration via TRPV1 activation. Together, these results indicate that mitochondrial TRPV1 plays an important role in inducing microglial migration. Activation of TRPV1 triggers an increase in intramitochondrial Ca2+ concentration and following depolarization of mitochondria, which results in mtROS production, MAPK activation, and enhancement of chemotactic activity in microglia. GLIA 2015;63:1870–1882